Online Compulsive Buying as a Coping Strategy for Self-Uncertainty: The Moderating Role of Gender in China. Issue 4 (2nd October 2022) - Liu, Yanan; Unger, Alexander; Bi, Chongzeng; Papastamatelou, Julie; Raab, Gerhard
Abstract: Self-uncertainty is of high relevance for a wide range of thinking and behavior, associated with compulsive buying patterns, since a high level of self-uncertainty is an interfering factor for a stable and consistent self. In turn, online compulsive buying is caused by a wide range of negative personality traits or states. Consequently, self-uncertainty can be viewed as a new important potential predictor for online compulsive buying. With the development of e-commerce, online compulsive buying has been identified as an increasing pathological buying pattern with severe consequences, such as debts, psychological distress and conflicts in partnerships, in particular for female and young consumers. Until now self-uncertainty has not been considered as a factor of influence on either compulsive buying or online compulsive buying. Present research aims to close this gap and investigate whether self-uncertainty affects online compulsive buying and if this effect is moderated by gender. Our sample consisted of Chinese University students (n = 404) who completed the Self-Uncertainty questionnaire, and a modified version of the Bergen Shopping Addiction Scale. We observed that self-uncertainty affects online compulsive buying and that self-uncertainty increases online compulsive buying for females, but not for males.